IMPLEMENTASI MEDIA PUZZLE UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK KELAS IV DI MI SUNAN BONANG II - Nabila Hopsawati; Firdaus Ainul Yaqin; Nani Zahrotul Mufidah (Fakultas Agama Islam Universitas Al Washliyah, 2025)
Education is a vital foundation for building and advancing a nation's civilization. Through education, the next generation can be shaped into quality individuals with knowledge, skills, and good character. This study aims to describe the factors causing low student interest in learning and analyze the implementation of puzzle learning media in Aqidah Akhlak subject for 4th-grade students at MI Sunan Bonang II. This qualitative research uses a descriptive qualitative method to detail the phenomenon or research object based on actual conditions. The subjects of this study were 15 fourth-grade students, consisting of 8 female students and 7 male students. The data collection instrument used was direct observation, where the researcher went directly to the location of MI Sunan Bonang II, located at Jl. Kyai Ahmad Lebbe, Brani Wetan Village, Maron District, Probolinggo Regency, and monitored the learning process in the classroom. The data collection techniques used in this study were observation, interviews, and documentation. The results showed a significant change, namely an increase in student interest in learning after using puzzle media in the Aqidah Akhlak subject.